(3GdfcJ hGdahGFO GdSfjI Ydi eTcd GdeMQQ dGHf JjejIs - (3eMeO Hf Ydj Hf eaGM Hf eaQL GdebOSi GdMfHdis; (3YHO GdSdGe Hf YHO Gddg Hf GdNVQ Hf eMeO, eLO GdOjf CHh GdHQcGJ GHf JjejI GdMQGfj,J (B652 (3g` s ((3CMeO Hf CHj HcQ Hf YHO GdQMef GdTgjQ HGHf QRjb GdebOSi GdMfHdi s)
(3ChdgG (B:s
(3bGd GdTjN hgPG GdcJGH GSeg GdfcJ hGdahGjO GdSfjI Ydi eTcd GdeMQQ s
(3BNQgG (B:s
(3hbGd ai GdQYGjI GdcHQi LGA HNGJe HaU hbGd eG CQOJ GdaU s
(3JcQQ CjVkG JMJ Qbe (B"18" (3abg MfHdis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B6s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B678s
Keywords: (3Gdabg GdMfHdjs